Surface plasmon resonance sensors : a materials guide to design, characterization, optimization, and usage /: a materials guide to design, characterization, optimization, and usage. ([2019]) - Oliveira, Leiva Casemiro; Lima, Antonio Marcus Nogueira, 1958-; Thirstrup, Carsten; Neff, Helmut Franz
No abstract available